Adaptation of health systems to climate change-related infectious disease outbreaks in the ASEAN: Protocol for a scoping review of national and regional policies - Miranda A.V. (2023)
BACKGROUND: The Association of South-East Asian Nations (ASEAN) member states (AMS) are among the countries most at risk to the impacts of climate change on health and outbreaks being a major hotspot of emerging infectious diseases. OBJECTIVE: To map the current policies and programs on the climate change adaptation in the ASEAN health systems, with particular focus on policies related to infectious diseases control. METHODS: This is a scoping review following the Joanna Briggs Institute (JBI) methodology. Literature search will be conducted on the ASEAN Secretariat website, government websites, Google, and six research databases (PubMed, ScienceDirect, Web of Science, Embase, World Health Organization (WHO) Institutional Repository Information Sharing (IRIS), and Google Scholar). The article screening will be based on specified inclusion and exclusion criteria. Policy analysis will be conducted in accordance with the WHO operational framework on climate-resilient health systems. Findings will be analyzed in the form of narrative report. The reporting of this scoping review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). ETHICS AND DISSEMINATION: Ethical approval is not required for this study as this is a scoping review protocol. Findings from this study will be disseminated through electronic channels.